Key performance indicators to improve the competitive dimensions of the construction company (Research, Society and Development, 2020)
The construction industry is a significant economic and productive sector of a country. Due to the importance of the sector, this study is justified not only for the academia, but also for the productive and business circles. Identifying competitive dimensions and comprehend the organizational performance through performance indicators, allows managers to make decisions through these tools, according to the model in which the organization operates, as close as possible to their reality. The present work aims to analyze the application of performance indicators through the competitive dimensions of the construction company. The used research method was a qualitative approach, being of an applied nature, classified according to the objectives of the research in descriptive and explanatory. The procedure used was the review of the literature through scientific articles in the Web of Science data bases, for the last ten years.